2014
DOI: 10.1002/ajhb.22641
|View full text |Cite
|
Sign up to set email alerts
|

Relative leg length is associated with type 2 diabetes differently according to pubertal timing: The Brazilian longitudinal study of adult health

Abstract: Objectives Studies from developed societies have shown that individuals with short legs relative to height have higher risk of type 2 diabetes. This has been much less explored in less developed populations where influences on relative leg length and diabetes may differ. The Brazilian Longitudinal Study of Adult Health (in Portuguese, ELSA-Brasil) allows us to test, in a cohort born (1934–1975) and raised when undernutrition was common, whether short legs relative to height is positively associated with diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…[8] After adjustment for potential early-life confounders and BMI at age 20 years, a one-unit decrement in relative leg-length Z score was associated with 12% higher prevalence of diabetes in men and women. This association was stronger in women who had earlier menarche onset.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] After adjustment for potential early-life confounders and BMI at age 20 years, a one-unit decrement in relative leg-length Z score was associated with 12% higher prevalence of diabetes in men and women. This association was stronger in women who had earlier menarche onset.…”
Section: Introductionmentioning
confidence: 99%
“…[8] There are several biologic mechanisms that may explain this interaction. Earlier age at menarche, which itself is associated with greater type 2 diabetes risk,[12] may represent greater early-life adiposity.…”
Section: Introductionmentioning
confidence: 99%
“…Among white populations living in high-income countries, shorter legs and lower LHR are consistently associated with higher measures of adiposity and diabetes-risk, including the PROMISE cohort in Canada as well as NHANES III and ARIC in the USA 11,20,30,31 . Still, the evidence has been scarce and inconclusive for individuals of African descent and for populations in less-developed regions, such as China and Brazil 10,11,30,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…27 Observations from other populations also showed an association between leg length and age at menarche. 28,58,59 A study based on the third National Health And Nutrition Survey found that earlier menarche was associated with shorter stature, mainly due to shorter leg length. 28 The association between age at menarche and leg length, however, depends on the contextual environment; earlier menarche predicts taller stature among developing countries, whereas it predicts shorter stature in developed countries.…”
Section: Discussionmentioning
confidence: 99%